THE EFFECT OF THE TWO STAY TWO STRAY (TSTS) LEARNING MODEL ON STUDENT LEARNING OUTCOMES IN GRADE IV PPK SUBJECTS AT UPTD SPF SD NEGERI 1 RIMO - Nuraya, Sopi; Safiah, Intan; Yamin, M. (Universitas Syiah Kuala, 2025)
The process of teaching and learning activities is still teacher-centered. However, in reality, students should be expected to be more active and play a bigger role in the teaching and learning process, while teachers are only facilitators for students. As a result, students' learning outcomes, especially grades in PPKn subjects, tend to be low. Students were less enthusiastic and there was no question and answer process during the discussion in participating in PPKn learning, because it was considered a boring lesson and difficult to understand... so the Two Stay Two Stray learning model was used. The formulation of the problem in this research is